Parental Knowledge and Practices Regarding Oral Hygiene of School Children of a School in Nepal - Sharma Poudel, Samikshya; Guragain, Manjeev; Sthapit Tuladhar, Sabita; Dahal, Samarika; Shrestha, Rejina; Bhochhibhoya, Amar (Journal of Nepalese Society of Periodontology and Oral Implantology, 2022)
Introduction: The influence of the parents that will determine the future of their children’s oral health. Parents are responsible for better oral hygiene practice of their children. There are very few studies accessing the knowledge regarding oral hygiene among the parents of schoolchildren. Objective: The objective of this study was to assess the level of knowledge and practice on oral hygiene among the parents of under five children. Methods: This was a descriptive cross-sectional study conducted for three months from 2017 June to 2017 August. A questionnaire was given to 102 parents of children below five years studying in Vidya Sadan High School. Questions related to demographic information and knowledge were asked. Knowledge score was calculated by allocating one point for each correct answer and zero point for each wrong answer. Then, calculated total knowledge scores were divided in four categories based on percentage. Results: Among 102 parents 42 (41.18%) were fathers, 64 (62.7%) of parents were literate. The median score about knowledge and practice on oral hygiene of the parents of under five children was identified, where the father’s score was six. Likewise, the comparison of ethnicity was also done and the median score of Newar was six. Conclusions: Most of the parents in the study had good knowledge and attitudes towards oral health of their children. However, some of them did not follow the recommendations for preventive paediatric dental care.